Vegetation response to abrupt climate changes in Western Europe from 45 to 14.7k cal a BP: the Bergsee lacustrine record (Black Forest, Germany). (22nd September 2017) - Duprat‐Oualid, Fanny; Rius, Damien; Bégeot, Carole; Magny, Michel; Millet, Laurent; Wulf, Sabine; Appelt, Oona
ABSTRACT: Between 45 and 14.7k cal a BP, the North Atlantic climate was characterized by a succession of short‐lived Greenland Stadials (GS)/Interstadials (GI), which impacted terrestrial environments. We present a new pollen record from the Bergsee (47°34′20″N, 7°56′11″E), which was ice free during the Last Glacial. We constructed a robust chronology for the period 45–14.7k cal a BP based on 14 accelerator mass spectrometry radiocarbon dates and a tephra attributed to the Laacher See Tephra. Vegetation history was reconstructed at the sub‐millennial scale using pollen analysis. At millennial timescale, a 45–30k cal a BP period shows relatively high tree percentages and marked forest developments, consistent with warmer and more humid conditions during Marine Isotope Stage (MIS) 3. This contrasts with a 30–14.7k cal a BP period of steppe conditions, favoured by a colder/more arid MIS 2. In detail, vegetation seems to respond to GIs and GSs with the successive development of steppes and boreal forests. The impact of Heinrich events is also recorded with a marked development of Artemisia . Comparison with European records shows the contribution of the Bergsee pollen record to understanding impacts of the North Atlantic climate variability on landscapes across longitudinal and latitudinal gradients.